Experimental constraints on the rheology, eruption, and emplacement dynamics of analog lavas comparable to Mercury's northern volcanic plains. Issue 7 (22nd July 2017) - Vetere, F.; Rossi, S.; Namur, O.; Morgavi, D.; Misiti, V.; Mancinelli, P.; Petrelli, M.; Pauselli, C.; Perugini, D.
Abstract: We present new viscosity measurements of a synthetic silicate system considered an analogue for the lava erupted on the surface of Mercury. In particular, we focus on the northern volcanic plains (NVP), which correspond to the largest lava flows on Mercury and possibly in the Solar System. High‐temperature viscosity measurements were performed at both superliquidus (up to 1736 K) and subliquidus conditions (1569–1502 K) to constrain the viscosity variations as a function of crystallinity (from 0 to 28%) and shear rate (from 0.1 to 5 s −1 ). Melt viscosity shows moderate variations (4–16 Pa s) in the temperature range of 1736–1600 K. Experiments performed below the liquidus temperature show an increase in viscosity as shear rate decreases from 5 to 0.1 s −1, resulting in a shear thinning behavior, with a decrease in viscosity of 1 log unit. The low viscosity of the studied composition may explain the ability of NVP lavas to cover long distances, on the order of hundreds of kilometers in a turbulent flow regime. Using our experimental data we estimate that lava flows with thickness of 1, 5, and 10 m are likely to have velocities of 4.8, 6.5, and 7.2 m/s, respectively, on a 5° ground slope. Numerical modeling incorporating both the heat loss of the lavas and its possible crystallization during emplacement allows us to infer that high effusion rates (>10, 000 m 3 /s) are necessary to cover the large distances indicated by satellite data from the MErcury Surface, Space ENvironment, GEochemistry, and Ranging spacecraft. Key Points: New viscosity data for Mercury northern volcanic plains lavas are presented Mercury lavas show shear thinning behavior with a decrease of viscosity of 1 log unit as shear rate ( γ ⋅ ) varies from 0.1 to 5.0 s −1 Heat loss during lava flow and emplacement implies that high effusion rates, >10, 000 m 3 /s, are required to cover large distances as observed by MESSENGER (NASA)